Evaluation of Technology Based Development in Enhancing Entomological Surveillance Program - Daswito, Rinaldi; Samosir, Kholilah; Pitriyanti, Luh (RRZ Scientific Publishing, 2025)
Routine monitoring of larvae is one of the efforts to interrupt the chain of DHF transmission in Tanjungpinang City. There is a requirement for innovation and establishment of android and web-based applications to enhance entomological surveillance. The research aimed to evaluate the technological-based development in enhancing entomological surveillance programs. Research and development design was used in this study with the Prototyping Method approach. Data was collected from interviews and document reviews. The data were used as the basis for making application prototypes, which will be tried to see shortcomings and then revised using a questionnaire. A total of 30 study samples were accidentally collected. The evaluation of the generated application was determined by variables such as usability, reliability, functionality, efficiency, maintainability, and portability. The research instrument deployed a questionnaire to get a quantitative value using a Likert scale for each variable, which was subsequently examined by univariate analysis. The study successfully developed a model for reporting mosquito larvae monitoring using an Android and web-based system, with the name of a CIBERNATIK android application. After carrying out testing both through questionnaires and interviews, the results of the feasibility of the application were excellent (83,3% usable, 83,3% reliable, 76,7% functional, 83,3% efficient, 70% maintainable, and 56% portable). CONCLUSION: The user can effectively implement the application, but further development is needed to integrate it into the Health Office program. The application serves as a database for real-time and easily accessible information on the density of larvae. Additionally, it functions as an early alert system for dengue control in Tanjungpinang City.